Aplikasi Penggunaan Sistem Barcode QR Code pada Gigi Sebagai Data Antemortem untuk Identifikasi Prajurit TNI - Sophian Abdurahman (DEFENDONESIA, 2024)
Background to antemortem identification in the context of forensic odontology, especially in the context of TNI soldiers. QR Code enables the effective storage of vital information such as the Soldier Registration Number (NRP) on the surface of the gear, facilitating a fast and accurate identification process in emergency or disaster situations. This research aims to implement QR Code as a method of antemortem identification of TNI soldiers' teeth. This method includes using the QR Code Generator application to create a QR Code and the QR Code Reader application to scan the QR Code from fallen teeth. The QR Code is placed on the tooth surface using etching, bonding and translucent composite coating techniques. Using the QR Code Generator application allows the creation of QR Codes from specific information such as NRP, while the QR Code Reader is used to verify and read information from the installed QR Code. The implementation of QR Codes on TNI soldiers' teeth has demonstrated success in maintaining the clarity and accuracy of antemortem identification information. QR Code allows medical teams to quickly access fallen soldier data, increasing efficiency in the identification process and reducing the risk of possible misidentification. The use of QR Code as a method of antemortem identification of TNI soldiers' teeth offers an effective and reliable solution in forensic odontology. By continuing to develop this technology, it is hoped that it can improve identification capabilities in critical medical and military situations, and support national security more effectively.